Biological P cycling is influenced by the form of P fertilizer in an Oxisol - Margenot, Andrew J.; Sommer, Rolf; Mukalama, John; Parikh, Sanjai J. (Springer, 2017)
Phosphate rock (PR) is an alternative fertilizer to increase the P content of P-deficient weathered soils. We evaluated the effects of fertilizer form on indicators of biological cycling of P using an on-farm trial on a Rhodic Kandiudox in western Kenya. Treatment plots were sampled after 13 cropping seasons of P applications as Minjingu phosphate rock (PR) or as triple super phosphate (﻿TSP) (50 kg P ha−1 season−1), as well as a P-unfertilized control (0 kg P ha−1 season−1). Soils (0–15 and 15–30 cm) were analyzed for microbial biomass P (Pmic), activities of acid phosphomonoesterase, alkaline phosphomonoesterase, and phosphodiesterase, and sequentially extractable P fractions. P additions as Minjingu PR yielded 299% greater Pmic than TSP at 0–15-cm depth despite similar labile P concentrations in the two P fertilization treatments and stimulated activities of acid phosphomonoesterase (+39%). When added in the soluble form of TSP, a greater percentage of total soil P was present in mineral-bound forms (+33% Fe- and Al-associated P). Higher soil pH under Minjingu PR (pH 5.35) versus TSP (pH 5.02) and the P-unfertilized treatment (pH 4.69) at 0–15-cm depth reflected a liming effect of Minjingu PR. The form of P fertilizer can influence biological P cycling in weathered soils, potentially improving P availability under Minjingu PR relative to TSP via enhanced microbial biomass P and enzymatic drivers of P cycling.